2014
DOI: 10.1177/1071100714539658
|View full text |Cite
|
Sign up to set email alerts
|

Single-Incision Lateral Approach for Triple Arthrodesis

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…97 Other surgeons prefer a lateral-only incision, which has rates of deformity correction, wound complications, and pain comparable to the dual-incision approach. 85,94 Given the concern for postoperative rigidity as well as the risk of nonunion, some surgeons have tried to spare the calcaneocuboid joint. In patients whose calcaneocuboid joints are not involved in their primary disease, a double arthrodesis still provides improvement in pain, function, satisfaction, cosmesis, and shoewear.…”
Section: Double/triple Arthrodesismentioning
confidence: 99%
See 1 more Smart Citation
“…97 Other surgeons prefer a lateral-only incision, which has rates of deformity correction, wound complications, and pain comparable to the dual-incision approach. 85,94 Given the concern for postoperative rigidity as well as the risk of nonunion, some surgeons have tried to spare the calcaneocuboid joint. In patients whose calcaneocuboid joints are not involved in their primary disease, a double arthrodesis still provides improvement in pain, function, satisfaction, cosmesis, and shoewear.…”
Section: Double/triple Arthrodesismentioning
confidence: 99%
“…97 Other surgeons prefer a lateral-only incision, which has rates of deformity correction, wound complications, and pain comparable to the dual-incision approach. 85,94…”
Section: Rigid Deformity Of the Footmentioning
confidence: 99%
“…These fusion rates are also similar to those reported in the literature, which range from 88% to 96%, depending on the techniques and joints studied. 5,9,11,16 Both constructs were safe and effective for use in hindfoot and midfoot arthrodesis procedures. Advantages of the new generation of nitinol staples are dynamic continuous compression that increases after time zero, full recovery of plantar gapping with 3-and 4-point bending, and new delivery instrumentation that does not require refrigeration or heating of the staple.…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective review demonstrated no increase in wound complications with a single lateral approach and noted no difference in woundhealing rates or complications while the single lateral approach enjoyed a shorter surgical time. 55 The medial "utility" incision spans from the medial malleolus to the navicular tuberosity and allows for access to the medial subtalar joint and most of the talonavicular joint. In the case of flatfoot deformity, this access is improved due to talar head uncoverage.…”
Section: Double Vs Triple Arthrodesismentioning
confidence: 99%
“…This retrospective review demonstrated no increase in wound complications with a single lateral approach and noted no difference in wound-healing rates or complications while the single lateral approach enjoyed a shorter surgical time. 55…”
Section: Approachmentioning
confidence: 99%